2022
DOI: 10.1021/acsomega.1c05515
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Activity of Triphenylphosphonium Derivatives of Natural Allylpolyalkoxybenzenes

Abstract: Derivatives of natural allylpolyalkoxybenzenes conjugated to triphenylphosphonium (TPP) cations by aliphatic linkers of three, six, seven, and eight atoms were synthesized to examine the role of the polyalkoxybenzene pharmacophore, TPP fragment, and linker length in antiproliferative activities. The key synthetic procedures included (i) hydroboration−oxidation of apiol, dillapiol, myristicin, and allyltetramethoxybenzene; (ii) acylation of polyalkoxybenzyl alcohols or amines; and (iii) condensation of polyalko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As adjuvants, in our scientific group, compounds of the terpenoid and flavonoid series are extensively studied, which show synergism with the main drug—antibiotics MF, levofloxacin, rifampicin, etc. Terpenoids and flavonoids are extracted from essential oils of plants that exhibit a number of remarkable biological effects [ 6 , 28 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], including analgesic, antibacterial, anti–inflammatory, and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…As adjuvants, in our scientific group, compounds of the terpenoid and flavonoid series are extensively studied, which show synergism with the main drug—antibiotics MF, levofloxacin, rifampicin, etc. Terpenoids and flavonoids are extracted from essential oils of plants that exhibit a number of remarkable biological effects [ 6 , 28 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], including analgesic, antibacterial, anti–inflammatory, and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the non-toxic components of natural extracts and oils attract attention as potential adjuvants to strengthen the main drug (antibacterial or antitumor drug) and reduce the off-target effects. The individual components of essential oils (allylbenzenes [44][45][46][47], terpenoids [48,49], terpenes [50][51][52], flavonoids [30,53,54], Thai herbs [55], etc.) have antioxidant, antibacterial, restorative and antitumor properties, and, moreover, they are effective inhibitors of efflux pumps [3,5,6,9,[14][15][16][17]20,21,28,[56][57][58][59][60] that cause bacterial resistance to antibiotics and the resistance of cancer cells to cytostatics.…”
Section: Introductionmentioning
confidence: 99%
“…Apiol analogues (myristicin, allyltetramethoxybenzene and dillapiol) have also demonstrated weak antitumor activity, but they have served as a booster for antitumor drugs (paclitaxel, doxorubicin, cisplatin) [49] due to the inhibition of mitochondrial enzymes [81,82], efflux pumps [49] and the increased permeability of the membrane of cancer cells [49,83]. It was previously shown that dillapiol (25-50 µM) induced G0/G1 cell cycle arrest, the activation of a number of caspases and, accordingly, the apoptosis of cancer cells, while apiol and its analogues had virtually no effect on benign epithelial cells in vitro [46]. Myristicin showed a similar but weaker effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triphenylphosphonium (TPP) cation is a powerful modifier for improving pharmacological properties of different natural products, including triterpenoids. , In addition to better solubility, TPP derivatives typically possess increased bioavailability at cellular and whole body levels due to the delocalized cationic and lipophilic nature of TPP, which provides effective transportation through cellular membranes by natural electrochemical gradients. , Such ability also underlies preferable accumulation of TPP derivatives in mitochondria in proportion to the membrane potential, which was shown to be increased in different cancer cells …”
mentioning
confidence: 99%